Creating mindful leaders : how to power down, power up, and power forward - Burton, Joseph, 1968- (John Wiley & Sons, Inc., 2018)
Unleash your inner mindful leader Mindfulness, emotional intelligence and resilience are the "must have skills" for modern leaders-yet many professionals are too stressed to know where to start. Creating Mindful Leaders provides deep insights and easy practices based in neuroscience, brain training and positive psychology to help professionals thrive in the "age of disruption." Written by a global COO turned successful tech entrepreneur, the book provides a roadmap to greater health, happiness and performance. It speaks to every professional wanting to reduce stress, achieve greater success and enjoy life more.-Offers immediately actionable techniques for professionals at all skill levels -Provides relatable, real-world advice -Helps build resilience while changing your relationship to stress -Shares a roadmap for sustainable performance in the face of ongoing change Creating Mindful Leaders provides an informed, humorous and expert peak into the sources of stress caused by the modern pace of living and offers practical, actionable tools and techniques as the antidote to manage stress, increase resilience, and improve your wellbeing, performance, relationships, sleep and physical health.